Avaliação ex vivo da precisão do localizador eletrônico Root ZX II na determinação da posição do limite CDC, utilizando-se o registro 1 do visor - Santana, Bianca Palma (2008)
It is generally accepted that root canal treatment procedures should be confined within the root canal system. To achieve this objective the canal terminus must be detected accurately during canal preparation and precise control of working length during the process must be maintained. Several techniques have been used for determining the apical canal terminus including electronic methods. The purpose of this ex vivo vitro study was to evaluate the ability of apex locator Root ZX II to locate the CDC limit under radiographic and macroscopic analysis. Thirty seven extracted permanent human teeth that had not been endodontically treated previously were selected. After conventional access, patency of the root canal was carefully checked with a #6 file. After storage in 1% NaOCl for a period of 1 h, the cervical and the middle portions of the root canal were slightly enlarged with endodontic files and Gates-Glidden burs to remove the pulp tissue as completely as possible under thorough irrigation with 1% NaOC1. The electronic working length measurement was conducted with 1% NaOCl as canal irrigant and a K-type file fitting loosely in the apical third of the canal. To measure the canal length with Root ZX II, all the samples and 1 lip clip of the apex locator were mounted in an alginate model. A file attached to the file holder was slowly inserted into the root canal until the meter on the apex locator dial indicated the meter reading Apex. The file was then withdrawn until the flashing bar on the meter designated the 1 mark. After the measurements, the files were fixed with self-curing resin in the pulpal chamber. All teeth were removed from alginate and radiographed with a zero-degree inclination in buccolingual plane. A digital sensor records the X-ray image and transfers the image to a computer. The distance from the end of the file to apex was measured by three investigators, and recorded. Then, the apical 5 mm of the root was shaved along the long axis of the tooth until the file could be seen through a thin layer of dentin. The remaining layer was then carefully removed using a scalpel blade. Each specimen was photographed and the distance from the end of the file to CDC limit was measured microscopically by three investigators, independently. The obtained distances were compared using a paired samples t test to determine the accuracy. The mean distance between the apex locator working length and CDC limit was - 0.42 ± 0.45 mm. The CDC limit (± 0.5 mm) was located 83.78% of the times. The distance from the end of the file to apex measured on both radiographic (-0.95 ± 0.43 mm) and macroscopic examinations (- 0.93 ± 0.44 mm) showed no statistical differences (p>0.05). It was concluded that the meter reading 1 on Root ZX II display allowed 83.78% precision providing a safety margin to prevent unintentional overinstrumentation.